A layer-by-layer strategy for the scalable preparation of uniform interfacial electrocatalysts with high structural tunability: a case study of a CoNP/N, P-graphene catalyst complex. Issue 1 (4th December 2019) - Lu, Limei; Zhang, Yihe; Yu, Xuelian; Zhang, Yi; Ma, Zequn; An, Qi
Abstract : Scalable engineered interfacial electrocatalyst: a combination of LbL can scalably prepare CoNP/N, P-graphene with high componential and structural tunability. This method is applicable on various 2D and 3D conductive substrates. Abstract : Electrocatalysts are important for providing clean energy and have attracted intense research attention. All electrocatalysts must function on electrode surfaces; however, interfacial engineering strategies for electrocatalytic structures remain understudied, and scalable preparation methods are especially rare. In this study, we propose a strategy that employs a layer-by-layer (LbL) assembly, subsequent in-film deposition, and calcination to prepare a complex Co nanoparticle (CoNP)/N, P-graphene catalyst on various 2D and 3D electrode surfaces. We delicately adjusted a variety of parameters and demonstrated that our LbL-based method can finely tune the total amount, the doping fraction, and the electronic structure of the complex catalysts, and provide optimal catalytic performance. When prepared on a large piece of carbon cloth, the catalysts showed a highly uniform catalytic performance, demonstrating the capability of our method for scalable fabrication. Our study emphasizes the delicate nature of the interfacial engineering of electrocatalysts, and promotes functional interface design and mechanism studies.